Origin of a chloroplast protein importer - Bölter, Bettina (The National Academy of Sciences, 1998)
During evolution, chloroplasts have relinquished the majority of their genes to the nucleus. The products of transferred genes are imported into the organelle with the help of an import machinery that is distributed across the inner and outer plastid membranes. The evolutionary origin of this machinery is puzzling because, in the putative predecessors, the cyanobacteria, the outer two membranes, the plasma membrane, and the lipopolysaccharide layer lack a functionally similar protein import system. A 75-kDa protein-conducting channel in the outer envelope of pea chloroplasts, Toc75, shares ≈22% amino acid identity to a similarly sized protein, designated SynToc75, encoded in the Synechocystis PCC6803 genome. Here we show that SynToc75 is located in the outer membrane (lipopolysaccharide layer) of Synechocystis PCC6803 and that SynToc75 forms a voltage-gated, high conductance channel with a high affinity for polyamines and peptides in reconstituted liposomes. These findings suggest that a component of the chloroplast protein import system, Toc75, was recruited from a preexisting channel-forming protein of the cyanobacterial outer membrane. Furthermore, the presence of a protein in the chloroplastic outer envelope homologous to a cyanobacterial protein provides support for the prokaryotic nature of this chloroplastic membrane.